A T-cell-dependent antibody response (TDAR) method in BALB/c mice based on a cytometric bead array. Issue 1 (31st December 2022) - Zhong, Wenhua; Chang, Penghuan; Gan, Lianfang; Zhong, Lifan; Yang, Zhaoxin
Abstract: Most current methods to assess T-cell-dependent antibody responses (TDAR) are semi-quantitative and based on measures of antibody titer generated against a standard antigen like keyhole limpet hemocyanin (KLH). The precision, sensitivity, and convenience of TDAR assays might be improved by applying rapid, sensitive, specific cytometric bead assays (CBA). In the study here, KLH antigen was covalently coupled onto the surface of cytometric beads using immune microsphere technology, and IgM antibody capture spheres were prepared for use in pretreatment processing of samples. The working parameters associated with this novel TDAR-CBA system were optimized in orthogonal experiments. The optimal concentration of the KLH coating solution in this system was 160 μg/ml, that of the anti-KLH IgG capture spheres 6.0 × 10 5 /ml, and the optimal dilution of fluorescein isothiocyanate (FITC)-conjugated Affini-Pure Goat Anti-Mouse IgG (H + L) was 60 μg/ml. Repeated tests indicated that this approach yielded good linearity ( r 2 = 0.9937) method, with a within-run precision of 3.1–4.9%, and a between-run precision of 4.4–4.9%. This new approach had a limit of detection of 113.43 ng/ml (linear range = 390.63–50 000), and an interference rate of just 0.04–3.51%. Based on these findings, it seems that a new mouse TDAR assay based on CBA can be developed that would appear to be more sensitive, accurate, and precise than the current TDAR assay approaches based on traditional ELISA.